2018
DOI: 10.1016/j.tsep.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of thermal and residual stress fields induced by lined pipe welding

Abstract: This paper investigates numerical thermal fields and residual stresses induced by single-pass weld overlay (lap-weld) and girth welding (butt-weld) in lined pipe using Tungsten Inert Gas (TIG) welding. A distributed power density of the moving heat source based on Goldak's ellipsoid heat flux distribution is used in a Finite Element (FE) simulation of the lined pipe welding process. In addition, radiation and convection have been incorporated in heat transfer coefficient user-subroutines for the FE code ABAQUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…A moving heat source based on Goldak’s ellipsoid heat source model was used. The FEM was validated using previous experiments of the same sections of carbon-manganese C-Mn steel pipe lined with stainless steel, and the results show good agreement [10]. Almeida et al performed a TIG butt-welding simulation on thin AISI 316L stainless steel plates, the induced residual stresses due to the double ellipsoidal heat source are found to be in good agreement with the results obtained from experiment [2].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…A moving heat source based on Goldak’s ellipsoid heat source model was used. The FEM was validated using previous experiments of the same sections of carbon-manganese C-Mn steel pipe lined with stainless steel, and the results show good agreement [10]. Almeida et al performed a TIG butt-welding simulation on thin AISI 316L stainless steel plates, the induced residual stresses due to the double ellipsoidal heat source are found to be in good agreement with the results obtained from experiment [2].…”
Section: Introductionmentioning
confidence: 72%
“…Numerical simulation using finite element methods (FEM) is the commonly used technique to predict and analyze welding residual stresses [9], which is less time-consuming, cost-effective and offers greater versatility compared to experimental measurements [1]. FE simulation of welding process using Goldak’s ellipsoidal heat source model has been applied to predict residual stresses and deformation, which results from the induced transient thermal field by many researchers, and the experimental validation shows good agreement [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the two types of connections, the welding connection has the following disadvantages: (1) the quality of field welding is difficult to guarantee, especially for steel tubes with a large diameter, and (2) residual stress is induced in this connection. Residual stress is a major factor that contributes to fatigue damage, stress corrosion cracking and brittle fracture (Obeid et al, 2018; Wu and Kim, 2018). For flanged connections, because there is a large flange, the appearance is not aesthetically pleasing, particularly for architecturally exposed structural steel.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the effects of heat input, groove shape, and layer number on WRS distribution were studied to find the approach to reduce WRS. Obeid et al 20 investigated numerical thermal fields and WRS induced by single-pass weld overlay (lapweld) and girth welding (butt-weld) in lined pipe using TIG welding. It was shown that the use of an inner layer known as a liner has a considerable influence on the thermal history and residual stress distributions.…”
Section: Introductionmentioning
confidence: 99%